Expression of the “4.2 ka event” in the southern Rocky Mountains, USA - D. T. Liefert; B. N. Shuman (Climate of the Past, 2022)
The use of the climatic anomaly known as the “4.2 ka event” as the stratigraphic division between the middle and late Holocene has prompted debate over its impact, geographic pattern, and significance. The anomaly has primarily been described as abrupt drying in the Northern Hemisphere at ca. 4 ka (ka, thousands of years before present), but evidence of the hydroclimate change is inconsistent among sites both globally and within North America. Climate records from the southern Rocky Mountains demonstrate the challenge with diagnosing the extent and severity of the anomaly. Dune-field chronologies and a pollen record in southeastern Wyoming reveal several centuries of low moisture at around 4.2 ka, and prominent low stands in lakes in Colorado suggest the drought was unique amid Holocene variability, but detailed carbonate oxygen isotope (δ18Ocarb) records from Colorado do not record drought at the same time. We find new evidence from δ18Ocarb in a small mountain lake in southeastern Wyoming of an abrupt reduction in effective moisture or snowpack from approximately 4.2–4 ka, which coincides in time with the other evidence of regional drying from the southern Rocky Mountains and the western Great Plains. We find that the δ18Ocarb in our record may reflect cool-season inputs into the lake, which do not appear to track the strong enrichment of heavy oxygen by evaporation during summer months today. The modern relationship differs from some widely applied conceptual models of lake–isotope systems and may indicate reduced winter precipitation rather than enhanced evaporation at ca. 4.2 ka. Inconsistencies among the North American records, particularly in δ18Ocarb trends, thus show that site-specific factors can prevent identification of the patterns of multi-century drought. However, the prominence of the drought at ca. 4 ka among a growing number of sites in the North American interior suggests it was a regionally substantial climate event amid other Holocene variability.